2015
DOI: 10.1248/bpb.b14-00745
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Olanzapine as an Antiemetic Agent Changes Glucose Homeostasis in Cisplatin-Treated Rats

Abstract: We investigated the effects of olanzapine on cisplatin-induced pica (the consumption of non-nutrient materials such as kaolin) and glucose homeostasis in rats to clarify the effects of olanzapine when used as an anti-emetic drug. Rats were injected intraperitoneally (i.p.) with either 5 mg/kg cisplatin or saline. Additionally, 2 or 10 mg/kg olanzapine were administered i.p. to the rats 10 min before the administration of cisplatin and subsequently administered every 24 h for 3 d. Kaolin and food intake was mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…More generally, these data also support the use of rats as a model to address gaps in the literature examining the efficacy of olanzapine and other anti-emetics. For example, only one previous study by Machida et al (2015) examined systemic OLZ on malaise in young Wistar rats and observed only a marginally significant cisplatin-induced pica, making determinations of OLZ effectiveness limited. We report IP OLZ significantly reduced cisplatin-induced pica (*30% reduction) at 24 hr and both IP and ICV OLZ decreased pica (by *28% and *42%; respectively) 48 hr following cisplatin treatment, suggesting that OLZ successfully reduces pica under more robust experimental conditions (i.e., when a strong and reliable induction of cisplatin-induced pica is observed).…”
Section: Discussionmentioning
confidence: 99%
“…More generally, these data also support the use of rats as a model to address gaps in the literature examining the efficacy of olanzapine and other anti-emetics. For example, only one previous study by Machida et al (2015) examined systemic OLZ on malaise in young Wistar rats and observed only a marginally significant cisplatin-induced pica, making determinations of OLZ effectiveness limited. We report IP OLZ significantly reduced cisplatin-induced pica (*30% reduction) at 24 hr and both IP and ICV OLZ decreased pica (by *28% and *42%; respectively) 48 hr following cisplatin treatment, suggesting that OLZ successfully reduces pica under more robust experimental conditions (i.e., when a strong and reliable induction of cisplatin-induced pica is observed).…”
Section: Discussionmentioning
confidence: 99%